High-strength hoop and preparation method thereof
By using specific composition materials in the hoop and treating the phosphating liquid, the problem of insufficient tensile strength and corrosion resistance of the hoop is solved, and its performance and service life are significantly improved.
Patent Information
- Application Number
- CN202411552385.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-01
AI Technical Summary
During repeated loading and unloading, the existing clamps have reduced tensile strength and are poor in corrosion resistance, which is prone to rust and corrosion, resulting in a shortened service life.
A specific composition of the hoop body is used, including elements such as C, Mn, Mo, V, Cu, Sn, Co, Al, Nb, Ce, Y and Hf, and is treated with a phosphating liquid to improve tensile strength and corrosion resistance.
It significantly improves the tensile strength and corrosion resistance of the clamp, extends the service life, and prevents the decline in tensile strength caused by corrosion.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of clamps, and in particular to a high-strength clamp and a preparation method thereof. Background Art
[0002] A clamp is a metal product used to fasten, connect or fix objects. It is widely used in various fields, including construction, electricity, communications, transportation, etc. In the construction field, clamps are often used to fix pipes, cable trays, cable ducts, etc. to ensure that they are stably fixed on the supporting structure. In the power industry, clamps are used to fix accessories of equipment such as poles and transformers, as well as to connect and fix cables. In the field of communications, clamps are often used to fix optical cables, communication lines, etc. The clamp needs to withstand a large clamping force and external load. However, under repeated loading and unloading, as the use time of the clamp increases, its tensile strength will decrease, eventually leading to the breakage of the clamp. Furthermore, at this stage, the corrosion resistance of the clamp is poor, and it is easy to rust and corrode in a corrosive environment for a long time, thereby indirectly reducing the strength and service life of the clamp. Therefore, improving the tensile strength of the clamp is a technical problem that needs to be solved urgently. Summary of the invention
[0003] The present invention provides a high-strength clamp and a preparation method thereof, which solves the problem of poor tensile strength of the clamp in the related art.
[0004] The technical solution of the present invention is as follows: The present invention provides a high-strength clamp, which is obtained by treating a clamp body with a phosphating solution. The clamp body is composed of the following components in percentage by weight: C 0.3%~0.4%, Mn 1.5%~2.5%, Mo 0.06%~0.9%, V 0.6%~1.2%, Cu 0.2%~0.3%, Sn0.04%~0.13%, Co 0.4%~1.2%, Al 0.05%~0.12%, Nb 0.005%~0.015%, Ce 0.01%~0.018%, Y0.01%~0.015%, Hf 0.02%~0.12%, and the rest are iron and its inevitable impurities.
[0005] As a further technical solution, the weight ratio of the sum of the weights of Sn and Hf to the weight ratio of the Mo is 1:2-4.
[0006] When the weight ratio of Sn and Hf to Mo is 1:2~4, the tensile strength of the clamp can be further improved.
[0007] As a further technical solution, the weights of Sn and Hf are equal.
[0008] When the weight ratio of Sn and Hf to Mo is 1:2~4 and the weights of Sn and Hf are equal, the tensile strength of the clamp can be further improved.
[0009] The present invention also proposes a method for preparing the high-strength clamp, comprising the following steps: S1, preparing materials according to the components in the weight percentage, smelting, casting and forming, to obtain a hoop blank; S2, descaling, rolling and machining the clamp blank to obtain a semi-finished clamp; S3, subjecting the semi-finished clamp to heat treatment to obtain a clamp body; S4, pickling and washing the clamp body with water, and then phosphating with phosphating solution to obtain the clamp.
[0010] As a further technical solution, the phosphating solution comprises the following components in parts by weight: 20-35 parts of phosphoric acid, 10-15 parts of nitrate, 10-15 parts of potassium dihydrogen phosphate, 5.5-13 parts of polyethyleneimine, 1-14 parts of ethylenediaminetetraacetic acid ammonium ferric, 2-5 parts of sodium nitrite, and 80 parts of water.
[0011] Phosphating the clamp body with phosphating liquid can effectively prevent corrosive substances from directly contacting the metal matrix of the clamp. The addition of polyethyleneimine and ammonium ferric ethylenediaminetetraacetate can help to form a better film on the surface of the clamp and improve the corrosion resistance of the clamp, thereby effectively preventing the tensile strength of the clamp from decreasing due to corrosion.
[0012] As a further technical solution, the weight ratio of the polyethyleneimine to the ammonium ferric ethylenediaminetetraacetate is 1-5:1.
[0013] When the weight ratio of polyethyleneimine to ammonium ferric ethylenediaminetetraacetate is 1 to 5:1, the corrosion resistance of the clamp can be further improved, and the decrease in the tensile strength of the clamp due to corrosion can be further effectively prevented.
[0014] As a further technical solution, the nitrate is one or more of potassium nitrate, manganese nitrate, and calcium nitrate.
[0015] As a further technical solution, in step S2, high-pressure water spraying is used for descaling, the pressure is 15-17 MPa, and the spraying time is 35-45 minutes.
[0016] As a further technical solution, in step S3, the heat treatment is divided into a first heat treatment and a second heat treatment. During the first heat treatment, the temperature is 800~900℃, and the insulation time is 40~60min; during the second heat treatment, the temperature is 600~650℃, and the insulation time is 100~120min.
[0017] As a further technical solution, in step S4, during the phosphating treatment, the temperature of the phosphating solution is 75-85° C., and the phosphating time is 15-20 min.
[0018] As a further technical solution, in step S4, during the pickling, a hydrochloric acid solution with a mass fraction of 6% to 12% is used.
[0019] The working principle and beneficial effects of the present invention are: In the present invention, the contents of various components in the clamp are comprehensively considered, and a stable overall structure is formed through the effective interaction between the components, which helps to improve the tensile strength of the clamp. Among them, by adding Sn, Hf and Mo and optimizing the contents of the three, their synergistic effect can be fully exerted, thereby significantly improving the tensile strength of the clamp. DETAILED DESCRIPTION
[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] In the following embodiments and comparative examples, the Mn content in the ferromanganese alloy is 75wt%; the V content in the ferrovanadium alloy is 50wt%; the Cu content in the copper-iron alloy is 90wt%; the Mo content in the ferromolybdenum alloy is 70wt%; the Sn content in the ferrotin alloy is 60wt%; the Co content in the iron-cobalt alloy is 40wt%; the Nb content in the ferroniobium alloy is 65wt%; the Ce content in the ferrocerium alloy is 20wt%; the Y content in the yttrium-iron alloy is 60wt%; the Hf content in the aluminum-hafnium alloy is 10wt%; the Fe content in the scrap steel is 97.3wt%; and the model of polyethyleneimine is G-1500.
[0022] Example 1 A high-strength clamp is obtained by treating a clamp body with a phosphating solution, wherein the clamp body is composed of the following components in percentage by weight: C 0.3%, Mn 1.5%, Mo 0.06%, V 0.6%, Cu 0.2%, Sn 0.04%, Co 0.4%, Al 0.05%, Nb0.005%, Ce 0.01%, Y 0.01%, Hf 0.02%, the rest is iron and its inevitable impurities; The phosphating solution includes the following components in parts by weight: 20 parts of phosphoric acid, 10 parts of potassium nitrate, 10 parts of potassium dihydrogen phosphate, 5.5 parts of polyethyleneimine, 1 part of ethylenediaminetetraacetic acid ammonium ferric, 2 parts of sodium nitrite, 80 parts of water; A method for preparing a high-strength clamp comprises the following steps: S1. Mixing ferromanganese alloy, ferrovanadium alloy, ferrocopper alloy, ferromolybdenum alloy, ferrotin alloy, ferrocobalt alloy, ferroniobium alloy, ferrocerium alloy, ferroydtrium alloy, hafnium-aluminum alloy and scrap steel according to the above weight percentages, smelting and casting to obtain a hoop blank; S2, spraying the hoop blank with high-pressure water at a pressure of 15 MPa for 45 minutes to remove scale, and after rolling and machining, obtaining a semi-finished hoop; S3, subjecting the semi-finished clamp to a first heat treatment at a temperature of 800° C. and keeping the temperature for 60 minutes; subjecting the semi-finished clamp to a second heat treatment at a temperature of 600° C. and keeping the temperature for 120 minutes, to obtain a clamp body; S4. After pickling and washing the clamp body with a hydrochloric acid solution with a mass fraction of 8%, phosphating the clamp body in a phosphating solution at a temperature of 75°C for 20 minutes, a clamp is obtained.
[0023] Example 2 A high-strength clamp is obtained by treating a clamp body with a phosphating solution, wherein the clamp body is composed of the following components in percentage by weight: C 0.35%, Mn 2.0%, Mo 0.36%, V 1%, Cu 0.25%, Sn 0.13%, Co 0.8%, Al 0.1%, Nb0.01%, Ce 0.014%, Y 0.012%, Hf 0.11%, the rest is iron and its inevitable impurities; The phosphating solution includes the following components in parts by weight: 30 parts of phosphoric acid, 12 parts of potassium nitrate, 13 parts of potassium dihydrogen phosphate, 5.8 parts of polyethyleneimine, 6.2 parts of ethylenediaminetetraacetic acid ammonium ferric, 3 parts of sodium nitrite, 80 parts of water; A method for preparing a high-strength clamp comprises the following steps: S1. Mixing ferromanganese alloy, ferrovanadium alloy, ferrocopper alloy, ferromolybdenum alloy, ferrotin alloy, ferrocobalt alloy, ferroniobium alloy, ferrocerium alloy, ferroydtrium alloy, hafnium-aluminum alloy and scrap steel according to the above weight percentages, smelting and casting to obtain a hoop blank; S2, spraying the hoop blank with high-pressure water at a pressure of 16 MPa for 40 minutes to remove scale, and obtaining a semi-finished hoop after rolling and machining; S3, subjecting the semi-finished clamp to a first heat treatment at a temperature of 850° C. and keeping the temperature for 50 minutes; subjecting the semi-finished clamp to a second heat treatment at a temperature of 630° C. and keeping the temperature for 110 minutes, to obtain a clamp body; S4. After pickling and washing the clamp body with a hydrochloric acid solution with a mass fraction of 8%, the clamp body is phosphated in a phosphating solution at a temperature of 80°C for 18 minutes to obtain a clamp.
[0024] Example 3 A high-strength clamp is obtained by treating a clamp body with a phosphating solution, wherein the clamp body is composed of the following components in percentage by weight: C 0.4%, Mn 2.5%, Mo 0.9%, V 1.2%, Cu 0.3%, Sn 0.13%, Co 1.2%, Al 0.12%, Nb0.015%, Ce 0.018%, Y 0.015%, Hf 0.12%, the rest is iron and its inevitable impurities; The phosphating solution includes the following components in parts by weight: 35 parts of phosphoric acid, 15 parts of potassium nitrate, 15 parts of potassium dihydrogen phosphate, 13 parts of polyethyleneimine, 14 parts of ethylenediaminetetraacetic acid ammonium ferric, 5 parts of sodium nitrite, 80 parts of water; A method for preparing a high-strength clamp comprises the following steps: S1. Mixing ferromanganese alloy, ferrovanadium alloy, ferrocopper alloy, ferromolybdenum alloy, ferrotin alloy, ferrocobalt alloy, ferroniobium alloy, ferrocerium alloy, ferroydtrium alloy, hafnium-aluminum alloy and scrap steel according to the above weight percentages, smelting and casting to obtain a hoop blank; S2, spraying the hoop blank with high-pressure water at a pressure of 17 MPa for 35 minutes to remove scale, and after rolling and machining, obtaining a semi-finished hoop; S3, subjecting the semi-finished clamp to a first heat treatment at a temperature of 900° C. and keeping the temperature for 40 minutes; subjecting the semi-finished clamp to a second heat treatment at a temperature of 650° C. and keeping the temperature for 100 minutes, to obtain a clamp body; S4. After pickling and washing the clamp body with a hydrochloric acid solution with a mass fraction of 8%, the clamp body is phosphated in a phosphating solution at a temperature of 85°C for 15 minutes to obtain the clamp.
[0025] Example 4 The only difference between this embodiment and embodiment 2 is that, in this embodiment, the weight percentage of Mo added is 0.52%, the weight percentage of Sn added is 0.05%, and the weight percentage of Hf added is 0.03%.
[0026] Example 5 The only difference between this embodiment and embodiment 2 is that, in this embodiment, the weight percentage of Mo added is 0.4%, the weight percentage of Sn added is 0.11%, and the weight percentage of Hf added is 0.09%.
[0027] Example 6 The only difference between this embodiment and embodiment 2 is that, in this embodiment, the weight percentage of Mo added is 0.48%, the weight percentage of Sn added is 0.07%, and the weight percentage of Hf added is 0.05%.
[0028] Example 7 The only difference between this embodiment and embodiment 6 is that, in this embodiment, the weight percentage of Mo added is 0.48%, the weight percentage of Sn added is 0.05%, and the weight percentage of Hf added is 0.07%.
[0029] Example 8 The only difference between this embodiment and embodiment 6 is that, in this embodiment, the weight percentage of Mo added is 0.48%, the weight percentage of Sn added is 0.06%, and the weight percentage of Hf added is 0.06%.
[0030] Example 9 The only difference between this embodiment and embodiment 8 is that in this embodiment, 11 parts of polyethyleneimine and 1 part of ethylenediaminetetraacetic acid ammonium ferric are added to the phosphating solution.
[0031] Example 10 The only difference between this embodiment and embodiment 8 is that in this embodiment, 6 parts of polyethyleneimine and 6 parts of ethylenediaminetetraacetic acid ammonium ferric are added to the phosphating solution.
[0032] Embodiment 11 The only difference between this embodiment and embodiment 8 is that in this embodiment, 10 parts of polyethyleneimine and 2 parts of ethylenediaminetetraacetic acid ammonium ferric are added to the phosphating solution.
[0033] Example 12 The only difference between this embodiment and embodiment 8 is that in this embodiment, 12 parts of polyethyleneimine are added to the phosphating solution, but no ethylenediaminetetraacetic acid ammonium ferric acid is added.
[0034] Example 13 The only difference between this embodiment and embodiment 8 is that in this embodiment, 12 parts of ammonium ferric ethylenediaminetetraacetate are added to the phosphating solution, but no polyethyleneimine is added.
[0035] Embodiment 14 The only difference between this embodiment and embodiment 8 is that in this embodiment, ethylenediaminetetraacetic acid ammonium ferric and polyethyleneimine are not added to the phosphating solution.
[0036] Comparative Example 1 The only difference between this comparative example and Example 1 is that in this comparative example, Hf is not added and the weight percentage of Sn added is 0.06%.
[0037] Comparative Example 2 The difference between this comparative example and Example 1 is that in this comparative example, Sn is not added and the weight percentage of Hf added is 0.06%.
[0038] Comparative Example 3 The only difference between this comparative example and Example 1 is that in this comparative example, Sn and Hf are not added, and the weight percentage of Mo added is 0.12%.
[0039] Comparative Example 4 The difference between this comparative example and Example 1 is that in this comparative example, Mo is not added, the weight percentage of Sn added is 0.08%, and the weight percentage of Hf added is 0.04%.
[0040] Comparative Example 5 The only difference between this comparative example and Example 1 is that in this comparative example, Sn, Hf and Mo are not added.
[0041] Experimental Example 1 Tensile Strength Test The clamps prepared in Examples 1 to 8 and Comparative Examples 1 to 5 were tested for tensile strength according to the method in GB / T 228-2002 “Room Temperature Tensile Test Method for Metallic Materials”; the test results are shown in Table 1 below.
[0042] Table 1 Tensile strength test results of Examples 1 to 8 and Comparative Examples 1 to 5
[0043] In Table 1, compared with Comparative Examples 1 to 5, the tensile strength of Example 1 is significantly improved, indicating that Sn, Hf and Mo have a synergistic effect and can significantly improve the tensile strength of the clamp.
[0044] Compared with Examples 2 and 4, the tensile strength of Examples 5-6 is improved, indicating that when the weight ratio of Sn and Hf to Mo is 1:2-4, the tensile strength of the hoop can be further improved.
[0045] Compared with Examples 6 to 7, the tensile strength of Example 8 is improved, indicating that when the weight ratio of Sn and Hf to Mo is 1:2 to 4 and the weights of Sn and Hf are equal, the tensile strength of the hoop can be further improved.
[0046] Experimental Example 2 Corrosion Resistance Test The clamps prepared in Examples 1 to 3 and 8 to 14 were immersed in a hydrochloric acid solution with a mass fraction of 20% for 24 hours, the mass loss of the clamp samples was measured, and the mass loss rate was calculated according to the following formula: mass loss rate (%) = (mass of the clamp before immersion - mass of the clamp after immersion) / mass of the clamp before immersion × 100%. The test results are shown in Table 2 below.
[0047] Table 2 Corrosion resistance test results of Examples 1 to 3 and Examples 8 to 14
[0048] In Table 2, the clamps prepared in Examples 1 to 3 were immersed in a hydrochloric acid solution with a mass fraction of 20% for 24 hours, and the mass loss rate was ≤0.015%, indicating that the clamps prepared in this scheme have good corrosion resistance and can reduce the effect of corrosion on tensile strength. Among them, compared with Examples 8 to 9, the clamps prepared in Examples 10 to 11 were immersed in a hydrochloric acid solution with a mass fraction of 20% for 24 hours, and the mass loss rate was reduced, indicating that when the weight ratio of polyethyleneimine to ammonium ferric ethylenediaminetetraacetate is 1 to 5:1, the corrosion resistance of the clamp can be further improved, thereby further reducing the effect of corrosion on tensile strength. Compared with Examples 12 to 14, the clamps prepared in Example 8 were immersed in a hydrochloric acid solution with a mass fraction of 20% for 24 hours, and the mass loss rate was reduced, indicating that the addition of polyethyleneimine and ammonium ferric ethylenediaminetetraacetate in the phosphating solution helps to improve the corrosion resistance of the clamp, thereby effectively preventing the decrease in the tensile strength of the clamp due to corrosion.
[0049] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-strength clamp, obtained by treating the clamp body with phosphating solution, characterized in that: The clamp body is composed of the following components in weight percentage: C 0.3%~0.4%, Mn 1.5%~2.5%, Mo 0.06%~0.9%, V 0.6%~1.2%, Cu 0.2%~0.3%, Sn 0.04%~0.13%, Co 0.4%~1.2%, Al 0.05%~0.12%, Nb 0.005%~0.015%, Ce 0.01%~0.018%, Y 0.01%~0.015%, Hf 0.02%~0.12%, and the rest are iron and other inevitable impurities.
2. A high-strength clamp according to claim 1, characterized in that: The weight ratio of the Sn and Hf to the Mo is 1:2-4.
3. A high-strength clamp according to claim 2, characterized in that: The weights of Sn and Hf are equal.
4. A method for preparing a high-strength clamp according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1, preparing materials according to the components in the weight percentage, smelting, casting and forming, to obtain a hoop blank; S2, descaling, rolling and machining the clamp blank to obtain a semi-finished clamp; S3, subjecting the semi-finished clamp to heat treatment to obtain a clamp body; S4, pickling and washing the clamp body with water, and then phosphating with phosphating solution to obtain the clamp.
5. The method for preparing a high-strength clamp according to claim 4, characterized in that: The phosphating solution comprises the following components in parts by weight: 20-35 parts of phosphoric acid, 10-15 parts of nitrate, 10-15 parts of potassium dihydrogen phosphate, 5.5-13 parts of polyethyleneimine, 1-14 parts of ethylenediaminetetraacetic acid ammonium ferric, 2-5 parts of sodium nitrite, and 80 parts of water.
6. The method for preparing a high-strength clamp according to claim 5, characterized in that: The weight ratio of the polyethyleneimine to the ammonium ferric ethylenediaminetetraacetate is 1-5:
1.
7. The method for preparing a high-strength clamp according to claim 5, characterized in that: The nitrate is one or more of potassium nitrate, manganese nitrate and calcium nitrate.
8. The method for preparing a high-strength clamp according to claim 4, characterized in that: In step S2, the descaling is performed by spraying with high-pressure water at a pressure of 15-17 MPa for a spraying time of 35-45 min.
9. The method for preparing a high-strength clamp according to claim 4, characterized in that: In step S3, the heat treatment is divided into a first heat treatment and a second heat treatment. During the first heat treatment, the temperature is 800-900°C and the insulation time is 40-60 minutes; during the second heat treatment, the temperature is 600-650°C and the insulation time is 100-120 minutes.
10. The method for preparing a high-strength clamp according to claim 4, characterized in that: In step S4, during the phosphating treatment, the temperature of the phosphating solution is 75-85° C., and the phosphating time is 15-20 min.
Citation Information
Patent Citations
High-strength fastener and processing method thereof
CN102943207A
Corrosion-resistant cable hoop and preparation method thereof
CN118581387A
High-strength, mechanically energy-absorbing and corrosion-resistant shaped bodies made of cast iron alloys and method for their production
DE102014217369A1
High strength steel sheet having excellent ductility and workability, and method for manufacturing same
US20220042130A1
Steel sheet and method for producing same
US20230399712A1
Cited By
High-strength double-suspension-wire hoop for communication
CN122279425A